Coiling of Very Large or Giant Cerebral Aneurysms: Long-Term Clinical and Serial Angiographic Results - Sluzewski, Menno; Menovsky, Tomas; van Rooij, Willem Jan; Wijnalda, Douwe (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Initial complete occlusion of very large or giant aneurysms often cannot be accomplished, and most will partially reopen over time. This study was performed to assess the clinical and angiographic outcome of patients with very large or giant cerebral aneurysms treated with detachable coils.METHODS: During 6 years, 29 patients with 31 very large or giant (20–55-mm) cerebral aneurysms were initially treated with detachable coils. Nineteen patients presented with subarachnoid hemorrhage (SAH), and eight patients had symptoms of mass effect. One patient had an incidental aneurysm, and one patient had an additional aneurysm.RESULTS: Twenty-three (79%) of 29 patients had a good clinical outcome at a median follow-up of 50 months. One of 19 patients presenting with SAH had repeat bleed (annual rebleeding rate, 1.45%). After initial coiling, seven of 31 aneurysms were incompletely occluded; this rate increased to 20 of 29 aneurysms at 6-month follow-up angiography. After 16 repeat coiling procedures in 13 aneurysms, 12 of 29 aneurysms in surviving patients were still incompletely occluded. After additional treatment other than coiling (parent-vessel occlusion and/or surgery) in eight aneurysms, three of 25 aneurysms in 24 surviving patients were incompletely occluded. Only 13 (42%) of 31 aneurysms had one coiling as a sole therapy.CONCLUSION: Coiling of very large or giant aneurysms can be considered. Long-term clinical outcomes were good in 79% of patients. The stability of the coil mesh over time was poor, requiring repeat coiling, surgery, and/or parent-vessel balloon occlusion in 58% of the aneurysms primarily treated with coils.